Design of Digital Image Watermarking Technique with Two Stage Vector Extraction in Transform Domain (Journal of Information Technology and Digital World, 2021)
Multimedia data in various forms is now readily available because of the widespread usage of Internet technology. Unauthorized individuals abuse multimedia material, for which they should not have access to, by disseminating it over several web pages, to defraud the original copyright owners. Numerous patient records have been compromised during the surge in COVID-19 incidents. Adding a watermark to any medical or defense documents is recommended since it protects the integrity of the information. This proposed work is recognized as a new unique method since an innovative technique is being implemented. The resilience of the watermarked picture is quite crucial in the context of steganography. As a result, the emphasis of this research study is on the resilience of watermarked picture methods. Moreover, the two-stage authentication for watermarking is built with key generation in the section on robust improvement. The Fast Fourier transform (FFT) is used in the entire execution process of the suggested framework in order to make computing more straightforward. With the Singular Value Decomposition (SVD) accumulation of processes, the overall suggested architecture becomes more resilient and efficient. A numerous quality metrics are utilized to find out how well the created technique is performing in terms of evaluation. In addition, several signal processing attacks are used to assess the effectiveness of the watermarking strategy.
Keywords: Digital watermarking; Fast Fourier Transform; robust; security; copyright protection; singular value decomposition